Visible Ventilation: A Return to Passive Cooling - Duluk, Sophia; Woudenberg, Toshi; Thompson, Wesley; Kwok, Alison G (ARCC Conference Repository, 2014)
In 2007, the University of Oregon signed the American College and University Presidents' Climate Commitment to take steps toward becoming a carbon neutral campus by reducing greenhouse gas emissions and integrating sustainability into their curriculum. With fossil fuels supplying 76% of total building sector energy consumption (Architecture2030), campuses must adopt energy efficiency policies, which establish more stringent energy targets for new and existing construction, while utilizing renewable energy sources.There are more then 60 double loaded corridor buildings on the University of Oregon campus that rely solely on mechanical cooling. Pacific Hall, which is one of these types of buildings, is the focus of this study. It is along, narrow building oriented north-south, and occupants on the east and west sides often complain of thermal discomfort in the morning and the afternoon. Over the years, renovations have covered transoms above doors, openings to the corridor have been blocked, and windows, though operable, are generally left closed. Our approach to determine the passive cooling potential includes: 1) climate analysis, 2) building measurements (enclosure and interior wall systems, building proportions, operable glazing ratio), 3) onsite measurements of building base case conditions (temperature, humidity, surface temperatures, air movement, CO2 levels), and 4) development of appropriate climate-responsive renovation strategies. The effectiveness of these strategies is evaluated through 5) prediction of comfort using the ASHRAE Standard55-2010, Thermal Environmental Conditions for Human Occupancy, 6) manual calculations using passive cooling guidelines and computer simulations to examine energy use comparisons, and 7) a carbon emissions saved calculation. We found that Pacific Hall can rely on passive cooling for 5 months of the year with minor interior renovations. Energy analysis revealed an EUI savings of 149.5 kWh/m2 (25.3 kBtu/ft2) per year. Such aprotocol reveals a fairly easy approach to examine other buildings on campus and estimate the overall campus carbon reduction that is possible through a shift from mechanical to passive cooling.